Efek Penambahan Sodium Hypochlorite Terhadap Kekuatan Tekan Dental Stone - Faradisa, Alya Sayyida; Rizal, Moh Basroni; Teguh, Paulus Budi (Jurnal Material Kedokteran Gigi, 2022)
Cross infection is the transfer of microorganisms that can occur from individual to individual or an object. COVID 19 is an infectious disease that can cause cross-infection in dentistry. One example is making a working model of gypsum material which can cause cross-infection from patients to dentists or technicians, so it is necessary to control infection by mixing sodium hypochlorite disinfectant solution into type III gypsum material (dental stone). This study aims to determine the effect of sodium hypochlorite disinfectant solution on the compressive strength of dental stones. The reduction in the compressive strength of type III gypsum mixed with sodium hypochlorite can be associated with a reduction in cohesion between crystals which may also affect the ability of the crystals to interlock, causing improper braiding and a reduction in cohesion between the crystals themselves and the presence of changes. which arises due to the formation of salts with low solubility when in large concentrations so that it can change the crystallization nucleus and consequently can affect the product properties of gypsum, this occurs due to the administration of sodium hypochlorite disinfectant solution with high concentrations so that it can significantly reduce the strength press on gypsum type III (dental stone) Sodium hypochlorite solution is not recommended to be used with the mixing technique because it can reduce the compressive strength of type III gypsum material (dental stone) and a good concentration of sodium hypochlorite is 3%.